Texture and grain refinement for enhanced strength and ductility in friction stir welding of cold-rolled thin-strip rapidly solidified AA5182 Al–Mg alloy - Hesam Pouraliakbar; Hamed Jamshidi Aval; Mohammad Reza Jandaghi; Andrew Howells; Mark Gallerneault; Johan Moverare; Vahid Fallah (Journal of Materials Research and Technology)
Thin-strip (TS) casting enhances Al–Mg alloy production by rapidly solidifying strips, resulting in finer grains, higher solute supersaturation, and fewer intermetallic phases making it ideal for automotive and packaging industries. This study, for the first time, investigates the microstructural evolution and mechanical properties of cold-rolled and friction stir welded (FSWed) TS AA5182 alloy, focusing on grain refinement, texture development, and mechanical performance. Microstructural analysis reveals significant grain refinement through rolling and FSW, with dynamic recrystallization playing a key role in texture evolution. While rolling enhances strength at the expense of elongation, FSW improves both tensile strength and toughness, particularly at lower pin rotational speeds. Texture analysis indicates that lower rotational speeds result in more pronounced texture, whereas higher speeds weaken overall texture strength. It was found that the formation of grains with the {101}<01‾0> orientation in the stir zone helps minimize stress concentration, promote uniform stress distribution, and reduce strain localization. Schmid factor analysis suggests that the balance of active slip systems and texture evolution contributes to the optimized mechanical performance observed in samples processed at lower rotational speeds. These findings emphasize the synergistic effects of grain refinement and texture strengthening, particularly the development of preferred orientations, in enhancing the strength and ductility of AA5182 alloy. This study offers valuable insights into the unique microstructural and mechanical transformation mechanisms in rolled and FSW samples, contributing to the optimization of TS alloys for industrial use and the development of more efficient and sustainable manufacturing techniques.